Calibration of a metal oxide sensor for ammonia detection targeting IoT solutions - Mulling, Lucas Fischer; Lindino, Cleber; Oyamada, Marcio Seiji (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2023: Anais do XIII Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2023)
The use of metal oxide sensors for air quality measurement is advantageous due to the low cost of the sensors, response time, and ease of operation. The MICS-6814 sensor consists of a package of three sensors that can measure various gases. Due to the metal oxide composition of the sensor, its response is affected by various external factors such as ambient temperature and relative humidity. In this work, we investigate the use and calibration of the MICS-6814 sensor in an IoT solution for the detection of ammonia (NH3) in closed environments. The calibration is based on correcting for the effects of ambient temperature and relative humidity using the multiple linear regression method. The calibration process was performed in laboratory, with tests of temperature and relative humidity variation and with ammonia (NH3) in a closed glass chamber. The developed system was able to detect the presence of ammonia in a closed room used to simulate the escape of this gas in an industrial environment.